Effect of Olfactory Stimulation in Agenesis of the Corpus Callosum: A Case Report. Issue 3 (29th December 2014) - Tonacci, Alessandro; Chilosi, Anna Maria; Pioggia, Giovanni; Morales, Maria Aurora; Cioni, Giovanni
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: To evaluate the olfactory and psychophysical performances in a 13-year-old boy with intellectual disability and severe hypoplasia of the corpus callosum and of the olfactory bulbs, compared to controls. Methods: The Sniffin' Sticks Identification Test was administered to the patient and to a patient control child with cognitive delay, with the same mental (5 years) and chronological age, but normal brain magnetic resonance image. Two typically developing control participants, aged 13 and 5, were also evaluated. Psychophysical tests were performed during the olfactory assessment by smart portable sensors. Results: A significant decrease in olfactory function and a different psychophysical response to stimuli were observed in the patient compared to control participants, suggesting absence of 'odorous stress'. A higher olfactory score but a similar psychophysical trend was found in the patient control with cognitive delay, while the two other control participants showed a selective increase of the anxiety state depending on the odour presented. Conclusions: Olfactory dysfunction is reported in children with neurodevelopmental disabilities. Low-cost, portable devices to assess olfactory function are proposed for use with children with intellectual disability. Stress monitoring by unobtrusive platforms provides discriminant information in this subset, as compared to controls.